A retrospective, observational, single center study of gonadotropin-releasing hormone agonist protocols at the Reproductive Center of Farah Hospital in Jordan - Kilani, Zaid; Shaban, Mohammad (International Journal of Research in Medical Sciences, 2019)
Background: Data on infertility and in vitro fertilization (IVF) are incomplete and uncertain in Jordan and worldwide because of difficulties in evaluating infertility in the general population. This study aimed at comparing the effectiveness of the gonadotropin-releasing hormone agonists (GnRH-a) long and short protocols as part of IVF or intracytoplasmic sperm injection. Methods: This observational, retrospective, comparative, longitudinal study was conducted in a reproductive center in Jordan. It reviewed data charts from women who took GnRH-a for IVF, from 2010 to 2013. These were categorized in Group A (long-term GnRH-a: single 3.75 mg-monthly injection) or Group B (short-term GnRH-a: multiple daily 0.1 mg injections). The primary endpoint was the rate of ongoing clinical pregnancy (number of pregnancies/number of women) and live birth rate in fresh cycle/protocols. Results: Out of 1,946 eligible women, 471 underwent the long-term treatment of GnRH-a administration and 1,523 the short-term treatment. The women’s mean age was 29.61±3.80 years old. Out of the 471 women in Group A, 216 (45.9%) women had ongoing clinical pregnancy, of whom 69 (31.9%) had live births. In the short-protocol group, 485 (31.8%) women had ongoing clinical pregnancy, of whom 133 (27.4%) had live births. Conclusions: GnRH-a long protocol is more effective than the short protocol regardless of the agonist formulation used in subfertile women/men who underwent IVF/ intracytoplasmic sperm injection.